Sinergi Efektif Karang Taruna dan Masyarakat dalam Mewujudkan Desa Tumbuan Yang Maju - Oktapiansyah, Randi; Sari, Novita; Carlina, Atin; Wahyu, Betran Akbar; Melinda, Dini; Agustina, Sindi; Andalena, Marlen; Oktalia, Tiara; Hasanah, Mufrotun; Sari, Resi Bella Realitas (An Naf'ah: Jurnal Pengabdian Masyarakat, 2024)
This service aims to analyse the role of Karang Taruna in supporting village development, particularly in the context of community empowerment and welfare improvement. The case study was conducted in Tumbuan Village with a focus on the synergy between Karang Taruna, the community, and the village government. Through various activities, such as leadership training, community-based economic development, and environmental conservation, Karang Taruna has successfully increased the leadership capacity of its members, increased community income, and improved environmental awareness. However, this Service also identified several challenges faced, such as limited resources and differences in views between generations. The results of this service show that synergy between Karang Taruna and the community is key in achieving sustainable village development. This success can be a model for other villages that want to develop their local potential